A case of primary multidrug-resistant pulmonary tuberculosis with high minimum inhibitory concentration value for bedaquiline. Issue 8 (August 2022) - Kobayashi, Masahiro; Motoki, Yuya; Yamagishi, Tetuya; Hirano, Hitomi; Nonaka, Mizu; Aono, Akio; Mitarai, Satoshi; Saito, Takefumi
Abstract: Bedaquiline is a new ATP synthesis inhibitor developed as an anti-tuberculosis agent. It has resistance-associated variants (RAV), regardless of preceding bedaquiline exposure. Herein, we describe the case of a patient with multidrug-resistant tuberculosis (MDR-TB) who had no history of bedaquiline therapy but presented a relatively high minimum inhibitory concentration (MIC) of bedaquiline (1 μg/mL). Whole genome sequencing revealed a mutation in the resistance-associated gene Rv0678 . The patient was first treated with a five-drug regimen (bedaquiline, delamanid, levofloxacin, cycloserine, and amikacin), which induced negative sputum culture conversion. Despite the successful treatment outcome, several questions remain regarding the efficacy of bedaquiline in this patient. Bedaquiline is an indispensable drug for MDR-TB treatment, but its clinical efficiency in the presence of Rv0678 mutations remains unclear. Therefore, evaluating the MIC of bedaquiline even in patients without a history of bedaquiline use is important for therapeutic regimen selection and may emphasize the importance of therapeutic drug monitoring in cases of bedaquiline RAV.